Comparison of two local anesthesia techniques (conventional & akinosi) for inferior alveolar dental nerve - Refua Y; Abbas-Zadeh. N (Tehran University of Medical Sciences, 2001)
Different techniques for local anesthesia are used in the mandible. The purpose of this study"nwas to determine the effects of inferior alveolar dental nerve blocks by comparing the two akinosi and"nconventional techniques. 80 patients (aged 15-60 years old) were randomly divided into tow groups for"nextracting the mandibuler posterior teeth by akinosi and conventional techniques. Patients were all"ninjected with 1.8 ml of Lidocaine 2% plus Adernaline j^nnnn .Then the Pain Sensation during injection,"npositive aspiration, beginning time of anesthesia, duration of anesthesia depth of anesthesia, and the anesthesia of soft tissue related to sensory nerves were evaluated. The results showed that the pain sensation in conventional technique was significantly higher than that of akinosi technique. The number of positive aspirations in conventional technique (12,5%) was higher than that of akinosi (5%) but not significantly different. The long buccal nerve anesthesia in akinosi technique (75%) was significantly higher than that of conventional technique. There was no significant difference between the two techniques for the depth of anesthesia. The success rate was 87.5% in conventional technique and 80% in akinosi technique. The average time of lips anesthesia in conventional technique was 3 minutes compared with 4 minutes in akinosi technique, which was not significantly different from each other. However, the beginning time of aneshtesia in tongue was significantly lower in conventional technique. No significant difference in the duration of anesthesia in lips and tonques between the two techniques was observed.